The effect of servant leadership and organizational culture on performance through the government work environment at the Patumbak Subdistrict Office in Deli Serdang Regency - Tafonao, Welisman; Prayoga, Boby Indra; Rambe, Saima (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This study aims to determine the influence of servant leadership and organizational culture on employee performance through the government work environment as an intervening variable at the Patumbak District Office. A quantitative approach with an associative method was used. The sample consisted of 25 respondents from the entire population using a total sampling technique. Data were collected through questionnaires and analyzed using SPSS version 25 with t-test, F-test, coefficient of determination (R²), and path analysis. The results showed that servant leadership had a positive and significant effect on employee performance, contributing 84%. Organizational culture also significantly influenced performance with a contribution of 85.4%. Furthermore, servant leadership and organizational culture significantly affected the work environment, contributing 85.8% and 89.2%, respectively. The work environment significantly influenced performance, contributing 88.2%. Simultaneous testing showed that servant leadership and organizational culture together had a significant influence on performance at 86.4%. Path analysis results showed that the indirect effects of servant leadership and organizational culture on performance through the work environment were 0.860 and 0.853, respectively. These findings indicate that the work environment mediates the relationship between the two independent variables and performance. The conclusion of this study is that servant leadership, organizational culture, and the work environment are essential interrelated factors in improving employee performance at the sub-district government level. Keywords: Organizational Culture, Performance, Servant Leadership, Work Environment